2022
DOI: 10.1002/ejoc.202201036
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Modification of Amino Acids and Peptides for the Rapid Synthesis of C‐Glycoamino Acids and C‐Glycopeptides

Abstract: Glycoamino acids and glycoproteins, especially C-glycoamino acids and C-glycoproteins, attract tremendous interests in the realm of biology and chemistry due to their wide occurrence in natural products, excellent pharmacodynamic properties and dynamic stability. Compared with the traditional construction of the amino acid or the glycosyl moiety de novo, postmodification of amino acids and peptides through direct glycosylation reactions constitute a powerful synthetic approach to attaining C-glycoamino acids a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 148 publications
0
3
0
2
Order By: Relevance
“…Functional group, such as bromo (2 c) at the ortho-position proved feasible, giving the product 11 in 81 % yield. In addition, styrenes 2 d-2 k bearing different substituents at the para-position, such as trifluoromethyl, halo, dimethylamino, were likewise amenable (12)(13)(14)(15)(16)(17)(18)(19). Noteworthy, the allyloxy group (2 j) was compatible with the ruthenium catalyst and thus allowed further application (18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional group, such as bromo (2 c) at the ortho-position proved feasible, giving the product 11 in 81 % yield. In addition, styrenes 2 d-2 k bearing different substituents at the para-position, such as trifluoromethyl, halo, dimethylamino, were likewise amenable (12)(13)(14)(15)(16)(17)(18)(19). Noteworthy, the allyloxy group (2 j) was compatible with the ruthenium catalyst and thus allowed further application (18).…”
Section: Methodsmentioning
confidence: 99%
“…[4] Thereafter, the Giese-type anomeric radical additions to activated alkenes with tin-hydride by irradiation set the stage for the C-alkyl glycosides synthesis, [5] among which tin-free variants, such as the combination of BEt 3 /O 2 as radical promoter, [6] visible light photoredox catalysis, [7] visible light activation, [8] samarium(II) mediated radical addition [9] and titanium catalysis, [10] improved its applicability (Scheme 1a). In recent years, straightforward CÀ H glycosylation [11] provided a reliable tools for the efficient and modular assembly of Cglycosides, [12] such as palladium-catalyzed ortho-CÀ H glycosylation. [13] In this context, our group found that the ruthenacycle A derived from ortho-CÀ H metalation allowed the glycosyl anomeric radical C addition at the para-position of the cycloruthenylated B CÀ Ru σ-bond, and thus achieved the formal meta-CÀ H glycosylation of arenes.…”
mentioning
confidence: 99%
“…[ 1 , 2 ] Considerable progress has been witnessed in the construction of C ‐glycosides in recent decades. [ 3 ] Novel and efficient synthetic techniques have displayed substantial potential in the synthesis of C ‐glycosides, especially C ‐aryl and C ‐alkenyl glycosides, involving methods such as C─H activation and cross‐coupling. [ 4 , 5 ] However, despite the importance of C ‐alkyl glycosides as building blocks for natural products and drugs, research on efficient construction methods for them remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…In den letzten Jahren hat sich die unkomplizierte CÀ H-Glykosylierung [11] als ein zuverlässiges Werkzeug für den effizienten und modularen Aufbau von C-Glykosiden erwiesen. [12] Unter anderem durch die Palladium-katalysierte ortho-CÀ H-Glykosylierung. [13] In diesem Zusammenhang fand unsere Gruppe heraus, dass der von der ortho-CÀ H-Metallierung abgeleitete Ruthenazyklus A die anomere C-Glykosyl-Addition an der para-Position der cycloruthenylierten C-Ru-σ-Bindung von B ermöglichte und so die formale meta-CÀ H- Glykosylierung von Arenen gelang.…”
unclassified
“…Funktionelle Gruppen wie Brom (2 c) in der ortho-Position erwiesen sich als praktikabel und ergaben das Produkt 11 in 81 % Ausbeute. Darüber hinaus waren die Styrole 2 d-2 k mit verschiedenen Substituenten in para-Stellung, wie Trifluormethyl, Halogenen, Dimethylamino, ebenfalls zugänglich (12)(13)(14)(15)(16)(17)(18)(19). Bemerkenswert ist, dass die Allyloxygruppe (2 j) mit dem Rutheniumkatalysator kompatibel war und somit eine weitere Anwendung ermöglichte (18).…”
unclassified